(untitled) (Historia, 2021)
The Great Trek denotes more than the literal departure from the CapeColony. It also denotes the settlement in the interior, the organization ofa state and community, the resultant political movements and the structureor pattern of the new state. The Great Trek extended over a long period,and must be viewed in that light. It must be considered up to the stagewhen it came to a more or less definite end and a new and different phaseset in. To my mind the years from 1836 to 1863 constitute the Trek period-the life span of about one generation. In that period the Trek enteredmaturity.It is the Trek period taken as a whole that we now wish to illustratefrom a geographical point of view. One should bear in mind that man isclosely bound up with his environment and that the political iflstitutionsand the movements or activities of human groups are influenced in various ’ays by their physical environment. When considering the political life,we might first of all determine the part played by g ographical featuresin the causes of the Trek, then investigate the movement itself, and finallyconsider the settlement and the forces arising therefrom